Relationship of Gingival Biotype with Schneiderian Membrane Thickness Using Cone Beam Computed Tomography (CBCT) - Sittara Javed, Maha Maqbool, Usman Manzoor Warraich, Khurram Ata Ullah, Zubair Ahmed Khan, Farheen Qureshi (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To find out the relationship of gingival biotype with schneiderian membrane thickness using cone beam computed tomography (CBCT) in patients at tertiary care dental hospital presenting for routine periodontal care. Methods: In this cross-sectional study, a total of 150 patients were observed in department of Periodontology, Fatima Memorial Hospital College of Medicine and Dentistry Lahore. Patients were clinically evaluated and gingival biotype wasrecorded. Afterthat cone beam computed tomography was performed to assess the patient’s schneiderian membrane thickness from mesial of maxillary 2nd premolar todistal of maxillary 2nd molar due to many anatomical variations of maxillarysinus. Results: In this study the mean age of the patients was 38.75±8.17 years, 70 (46.67%)patients were male. Thin biotype was found in 66(44%) patients and thickbiotype was found in 84 (56%) patients. In thin biotype the mean thickness of schneiderian membrane was 0.58±0.085mm while in thick biotype the mean of schneiderian membrane was1.25±0.07mm (p-value<0.05). Conclusion: The study concluded that there is significant relationship exist between the schneiderian membrane and thickness of biotype. positive correlation of gingival biotype with width of keratinizedgingivainmaxillaryanteriorteeth. Keywords: gingival biotype, schneiderian membrane, Cone Beam Computed Tomography (CBCT), missing teeth